2003
DOI: 10.1127/0941-2948/2003/0012-0257
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence-driven saltation in the atmospheric surface layer

Abstract: The relations between the turbulent structures that contribute to the Reynolds shear stress and the transport of saltating grains and between the wind speed and the saltation are studied. The saltation of sand particles and the turbulent flow field over a beach surface in the Western Baltic Sea are measured with a saltiphone, a sonic anemometer and cup anemometers. Continuous, synchronous measurements of horizontal sand transport at 0.1 m above ground and turbulent velocity fluctuations at 0.55 m were made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 0 publications
4
48
0
Order By: Relevance
“…This is particularly problematic in the field, where the dynamic complexity of the flow structures cannot be controlled in the same way as in modelled or wind tunnel environments [104]. This issue is pertinent given the evidence that turbulence is an important driving force behind sediment entrainment and transport in aeolian environments [105][106][107][108][109][110][111][112][113][114].…”
Section: Effects On Dragmentioning
confidence: 99%
“…This is particularly problematic in the field, where the dynamic complexity of the flow structures cannot be controlled in the same way as in modelled or wind tunnel environments [104]. This issue is pertinent given the evidence that turbulence is an important driving force behind sediment entrainment and transport in aeolian environments [105][106][107][108][109][110][111][112][113][114].…”
Section: Effects On Dragmentioning
confidence: 99%
“…A variety of designs exist but all operate on a similar basis of responding to the individual impacts of saltating grains on a sensitive surface. In the case of the Saltiphone, this surface is a highly responsive microphone (Arens, 1996;Schönfeldt and von Löwis, 2003;Sterk, Jacobs and van Boxel, 1998;Zobeck et al, 2003), while in the case of the Sensit and Safire, the surface is a piezoelectric transducer (Gillette and Stockton, 1989;Stout and Zobeck, 1997;Baas, 2004). The advantage of such instruments over traditional sand traps is that they are small, offer little resistance to the flow and are omnidirectional in response.…”
Section: Prediction and Measurement Of Sediment Fluxmentioning
confidence: 99%
“…While variability in surface conditions can account for some irregularity in entrainment, it is now clear that, in a similar manner to river flows (Bennett and Best, 1996;Kostaschuk and Villard, 1996;Venditti and Bauer, 2005), turbulence in the boundary layer is also a major driving force behind aeolian sediment entrainment and transport (Livingstone, Wiggs and Weaver, 2007;Weaver, 2008;Sterk, Jacobs and van Boxel, 1998;Schönfeldt and von Löwis, 2003). Indeed, it has also been shown that the influence of peak instantaneous turbulent stresses on sand transport dynamics is required to explain the observed development of mobile sand dunes (Castro and Wiggs, 1994;Wiggs, Livingstone and Warren, 1996;Walker andNickling, 2002, 2003;Weaver and Wiggs, 2010) and sand streamers (Baas, 2008).…”
Section: 9mentioning
confidence: 99%
See 1 more Smart Citation
“…Saltation, a mode of airborne particle motion in the atmosphere, plays a key role in aeolian sand transport studies (Schönfeldt and von Löwis, 2003). The transportation of most aeolian sediments due to wind erosion is by means of saltation Chepil, 1945).Research level of dust flux is very important to clear dust transport mechanism, on the one hand, strengthen the quantitative study on dust transport, on the other hand provide important parameters for numerical simulation of dust transport.…”
Section: Introductionmentioning
confidence: 99%